Immunohistochemical study of tubular epithelial cells and vascular endothelial cells in glomerulonephritis. (September 2014) - Bob, Flaviu; Gluhovschi, Gheorghe; Herman, Diana; Petrica, Ligia; Bozdog, Gheorghe; Gluhovschi, Cristina; Velciov, Silvia; Gadalean, Florica; Timar, Romulus; Potencz, Elena; Dema, Alis; Schiller, Adalbert
Abstract Background and aims: In order to assess the role played by tubular epithelial cells (TEC) and interstitial vascular endothelial cells (VEC) in interstitial fibrogenesis in human glomerulonephritis, we studied the expression of markers of activated fibroblasts (α-smooth muscle actin (αSMA) and vimentin (Vim)) and of the transforming growth factor β (TGFβ), at the level of these cells. Methods: We studied retrospectively 41 renal biopsies from patients with primary and secondary glomerulonephritis [24 males, 17 females, mean age 45.5 ± 12.9 years]. Immunohistochemistry using monoclonal antibodies (SMA, Vim, TGFβ) was assessed using a semiquantitative score, that was correlated with biological and histological data (quantified using a scoring system in order to assess active-inflammatory and chronic–sclerotic/fibrotic lesions). Results: The presence of SMA and Vim as markers of myofibroblasts was found in TECs and VECs. TEC Vim expression correlated with interstitial Vim expression (r = 0.38; p = 0.008), interstitial infiltrate (r = 0.31; p = 0.027), interstitial fibrosis (R = 0.25; p = 0.042), GFR (r = −0.35; p = 0.016), SMA (r = −0.42; p = 0.015), TGFβ (r = 0.25; p = 0.046), and hemoglobin (r = −0.55; p < 0.001). VEC Vim expression showed indirect correlations with interstitial infiltrate (r = −0.32; p = 0.023) and interstitial fibrosis (r = −0.34; p = 0.017). Conclusion: Our study reflects the complexity of the involvement of VEC and mainly of TEC in fibrosis. The expression of mesenchymal markers at the tubular cell level (especially Vim) correlates with histological interstitial changes, with the decrease of renal function and more strongly with anemia.